Positioning Research for Wireless Sensor Networks Based on PSO Algorithm - Zhang, Fengrong (Elektronika ir Elektrotechnika, 2013)
Based on the traditional DV-Hop algorithm and in order to overcome its existing drawbacks, an improved DV-Hop algorithm is brought forward in this paper by using the PSO algorithm. Through simulation experiments, it is found that both the average localization error and the localization coverage rate of PSO are better than that of DV-Hop. Moreover, with the increase of the number of nodes, the average localization error of PSO shows a downward trend and is less than that of DV-Hop. DOI: http://dx.doi.org/10.5755/j01.eee.19.9.5522